KONSELING ONLINE DAN SELF-DISCLOSURE PESERTA DIDIK: TINJAUAN SISTEMATIS LITERATUR PADA KONTEKS SEKOLAH MENENGAH - Yulia Saputri; Laora Benro; Muthi’ah Ilfa AF; Wahidah Fitriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Online counseling has become an increasingly common service in secondary schools as digital technology reshapes how students seek psychological and academic support. A central issue in this transition is self-disclosure, students' willingness to reveal personal thoughts, feelings, and problems to a counselor, since the depth and honesty of disclosure largely determine counseling effectiveness. This study systematically reviews empirical and conceptual literature published between 2020 and 2026 on the relationship between online counseling and students' selfdisclosure in secondary school settings. The review finds that anonymity, perceived privacy, reduced visual cues, and flexible communication channels in text-based and video-based online counseling tend to lower psychological barriers and encourage students to disclose more openly, particularly on sensitive topics such as family conflict, anxiety, and peer relationships. However, the level of self-disclosure is moderated by counselor presence, platform security, digital literacy, parental supervision, and the quality of the counselor-student relationship. The review also identifies persistent challenges, including unstable internet access, confidentiality concerns, and limited counselor training in online ethics, particularly in the Indonesian school context. These findings imply that online counseling can effectively complement face-to-face counseling in fostering self-disclosure among secondary school students, provided schools establish clear privacy protocols and strengthen counselors' digital competence.